Pengembangan Services Untuk Menghubungkan Aplikasi Human Resource Information System (HRIS) Dengan Modul Hr SAP - Meyliana, Meyliana (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Rapid business changes also trigger changes in interconnected applications. Changing multiple interrelated applications, have a level of difficulty and complexity of its own, especially if the platform and framework of these applications are not the same. One of the concepts that can help bridge the time gap problem between business change with changes in applications and platforms and frameworks to bridge the gap between applications is the implementation of "services". By using "services", interconnected applications will be able to produce more realtime information. A case study for the development of "service" is performed at the Human Resource (HR) department, which uses two different applications of Human Resource Information System (HRIS) for the frontend and use the SAP HR module as its backend. Bottom-up strategy is chosen as a strategy in developing the "service". Application of "service" is expected to help accelerate change in the development of applications and facilitate the further application, and can result in real-time information.